EMOTIONAL GEOGRAPHIES OF EFL SENIOR HIGH SCHOOL TEACHERS IN ONLINE TEACHING IMPLEMENTATION DURING THE COVID-19 PANDEMIC - Muhammad Zaid Muttaqin; Puji Sri Rahayu; Fajrianor Fajrianor (LET: Linguistics, Literature and English Teaching Journal, 2022)
This study was carried out to know what emotional geographic experiences EFL senior high school teachers experienced while teaching online during the Covid-19 pandemic and how they dealt with these emotional geographic problems. This research is qualitative research using the descriptive method. The participants in this study were 4 high school EFL teachers from 4 different high schools in Banjarmasin. Data were collected through an interview process. The study results show that of Hargreaves' 5 emotional geographies frameworks, each participant expresses various emotions. Some negative emotions such as anger, irritation, or dissatisfaction, and some positive emotions such as satisfaction or pleasure. In addition, the participants also shared their various ways of dealing with the emotional geographies problems according to each of the problems they raised such as reporting the problem to the counseling teacher, giving the student motivation, and more.